Effects of exsanguinations under anesthesia (Ketamine+Xylazine) as a mode of euthanasia on blood parameters and organ pathology in sprague dawley rats - Nor Hashimah Ismail
Euthanizing technique can be divided into two (2) groups; (i) chemical methods, which involves the administration of an overdose drugs through injection or inhalation or (ii) physical method, without using the chemical methods such as cervical dislocation that is primarily employed in small laboratory animals. Despite the various methods that can be chosen, each will have an effect on the samples collected. The use of carbon dioxide through inhalation and pentobarbital injection were the common methods used for euthanizing the laboratory animals. In this study, the effects of using anesthesia drugs (Ketamine+Xylazine) followed with exsanguinations in Sprague Dawley rats towards blood parameters and organs pathology were studied. A total of 20 Sprague Dawley rats were divided into 3 groups; (i) 100% carbon dioxide inhalation, (ii) Pentobarbital injection (100mg/kg) and (iii) Ketamine (100mg/kg) + Xylazine (10mg/kg) with exsanguinations. Results obtained revealed that there were differences in blood parameters and organs pathology. From the result, it showed that carbon dioxide and pentobarbital gave more effects on the blood parameters and organs pathology changes compared with used of Ketamine+Xylazine.